2009
DOI: 10.4038/jnsfsr.v37i3.1217
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution of aluminium from sub-standard utensils under high fluoride stress: a possible risk factor for chronic renal failure in the North-Central Province

Abstract: Chronic renal failure of an endemic nature and unknown aetiology affects people in the North-Central Province of Sri Lanka. People affected, consume fluoride rich water and almost exclusively use sub-standard aluminium pots for cooking and storing water. Leaching of aluminium under different fluoride stress and under the acidic conditions used in cooking was studied. Aluminium was determined using a graphite furnace Atomic Absorption Spectrophotometer. In the absence of acidic spices, the amount of aluminium l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 6 publications
(8 reference statements)
0
65
0
Order By: Relevance
“…Fluoride in combination with aluminium (Al) (such as from the substandard aluminium utensils used for boiling water and cooking) may produce alumino-fluoride complexes, which could become soluble and thus toxic, and contribute to the development or exacerbation of CKD-mfo [55]. These complexes may enhance the uptake of fluoride into the body because they can pass through biological membranes more easily than can fluoride and aluminium separately.…”
Section: Fluoride Theorymentioning
confidence: 99%
“…Fluoride in combination with aluminium (Al) (such as from the substandard aluminium utensils used for boiling water and cooking) may produce alumino-fluoride complexes, which could become soluble and thus toxic, and contribute to the development or exacerbation of CKD-mfo [55]. These complexes may enhance the uptake of fluoride into the body because they can pass through biological membranes more easily than can fluoride and aluminium separately.…”
Section: Fluoride Theorymentioning
confidence: 99%
“…Professor Illeperuma is the originator of the hypothesis of the association between fluoride and CKD-mfo [5]. He confirmed that data and detailed maps of Sri Lanka on the distribution of fluoride, hard water, and the prevalence of CKD in the North Central Province (NCP) and elsewhere have been available for more than a ''decade''.…”
Section: Letter From Professor Oliver Illeperumamentioning
confidence: 57%
“…I agree with Professor Fernando that many of the currently postulated hypotheses of potential causes of CKDmfo, including glyphosate, fluoride, heavy metals, aristolochic acid, illegal alcohol, tobacco, ionicity, and infectious aetiology, have been made without scientific evidence or credible experimental data [1,[4][5][6]. This further emphasizes the importance of implementing a nationwide, real-time surveillance programme and a wellcoordinated, broad multi-disciplinary, long-term research programme to identify and eliminate CKD-mfo from Sri Lanka.…”
Section: Letter From Professor Ravindra Fernandomentioning
confidence: 99%
“…Involvement of heavy metals such as Cadmium and Arsenic has been suggested but, the results have been inconsistent [6][7][8][9]. Fluoride has also been one of the earliest suggestions as an etiological factor for CKDu [10]. In addition, involvement of herbicides, mycotoxins, pesticides, and algal toxins in CKDu has been proposed and debated in the recent past [9,11].…”
Section: Introductionmentioning
confidence: 99%